2021
DOI: 10.3390/en14051334
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Catalytic Hydrogen Production from Formic Acid over Supported Metal Complexes

Abstract: Formic acid is a liquid organic hydrogen carrier giving hydrogen on demand using catalysts. Metal complexes are known to be used as efficient catalysts for the hydrogen production from formic acid decomposition. Their performance could be better than those of supported catalysts with metal nanoparticles. However, difficulties to separate metal complexes from the reaction mixture limit their industrial applications. This problem can be resolved by supporting metal complexes on the surface of different supports,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…This catalyst likely will not perform well when using diluted formic acid. 19,20 The Ru and Ir-based homogeneous catalysts on the contrary work better in aqueous medium compared to organic solvent. 21 Iguchi et al reported the formic acid decomposition reaction on the Ir-catalysts to reach maximal turnover frequency at formic acid concentrations between 14 and 25 wt%.…”
Section: Indirect Formic Acid Fuel Cellsmentioning
confidence: 99%
“…This catalyst likely will not perform well when using diluted formic acid. 19,20 The Ru and Ir-based homogeneous catalysts on the contrary work better in aqueous medium compared to organic solvent. 21 Iguchi et al reported the formic acid decomposition reaction on the Ir-catalysts to reach maximal turnover frequency at formic acid concentrations between 14 and 25 wt%.…”
Section: Indirect Formic Acid Fuel Cellsmentioning
confidence: 99%
“…Herein we report on the usage of the slag, which has been decorated with nanostructured-palladium on its surface ( i.e. Pd@slag, 1 ) and successively used in a two-step reaction, which consisted in a two-step reaction of the photocatalytic reduction of CO 2 and water into formic acid followed by its thermal decomposition into hydrogen and methanol (Scheme 1 , path b), the latter being one of the most important chemicals for industry 5 , 6 , 12 . Both photoconversion and thermal decomposition occurred with good yields, unprecedent selectivity and under relatively mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable and green energy alternatives, including solar power, wind power, hydropower, tidal power, biopower, and hydrogen energy, have been attracting a considerable amount of interest as a result of the gradual conventional fossil fuel consumption and increasingly severe environmental pollution after entering the 21st century. Among them, hydrogen (H 2 ) is comprehensively deemed as one of the most potential energy alternatives due to its merits of high energy capacity (142 MJ/kg, triple-fold as that of petrol), abundant reserves in the earth, and efficiency with environmentally friendly nature, as well as its classic application in the proton exchange membrane fuel cells. In this context, increasing attention has been paid to on-demand H 2 evolution from formic acid (FA) as a green and promising H 2 storage and production material because of its excellent volumetric (53.4 g/L) and gravimetric (4.4 wt %) hydrogen capacities, ease of handling and transporting, stability and nontoxicity at room temperature, as well as simple regeneration from cheap and abundant biomass. Hence, a myriad of homogeneous and heterogeneous catalytic systems are successfully developed for facilitating FA dehydrogenation (eq ) and avoiding CO poisoning from FA dehydration (eq 2 ) in the on-demand in situ H 2 evolution. In particular, AgPd bimetal nanostructures (core–shell or alloy) with controlled compositions and morphologies have played a vital role in H 2 evolution from FA because of their ligand effect and strain effect as well as superior catalytic activities. For example, Lu group first reported a highly efficient robust solid catalyst of PdAg–CeO 2 /MC by anchoring amorphous CeO 2 -modified PdAg alloy onto porous ca...…”
Section: Introductionmentioning
confidence: 99%